Formulation and Antibacterial Activity Test of Ethanol Extract Gel of Laruna Root (Chromolaena odorata L.) Against Staphylococcus aureus and Propionibacterium acnes - St. Rahmadani; Awaluddin, Nurhikma; Awaluddin, Akbar (Jurnal FARMASIMED (JFM), 2024)
Background: The formulation of gel preparations from laruna root extract (Chromolaena odorata L.) has been carried out using Na-CMC base accompanied by physical stability tests of the gel preparations. Objectives: to determine the physical stability of the laruna root extract gel preparation and its good concentration against Staphylococcus aureus and Propionibacterium acnes bacteria. Research method: The physical stability of the gel preparation was determined based on observations of changes in color, odor, shape, pH, uniformity, spreadability, and viscosity before and after storage for 6 cycles at temperatures of 4o C and 40oC. The pH test was carried out using a pH meter and viscosity measurements were carried out using a Brokfield viscometer. Results: The results of the study showed that the laruna root extract gel preparation was declared stable in the homogeneity indicator Results: The results showed that the gel preparation of laruna root extract could be said to be stable on homogeneity parameters where there were no solid particles in the preparation. Stable in good spreading power diameter, i.e. formulas 0, I, II, and III have a diameter of no more than 5-7 cm. For the results of measuring the viscosity of the gel preparation of laruna root extract, it is said to be stable because it is not more than 2000-4000 mPaS. For pH measurement, it is said to be stable because it has a pH in accordance with the quality requirements of skin preparations, which is 4.5-8.0. Conclusion: In the antibacterial activity test, a good clear zone result was obtained at a concentration of 0.3%.